ATOMIC REACTIONS - Van Zanten, Leonard (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Man constructed the atomic bomb without knowing its fundamentals, creating his vision of things by sight deception. He has his seasons but does not know how these come about, other than by error in sight deception. And so it is with most of his theories, while it will enhance him to come to a truth, as it will be in the centuries to come.